2019
DOI: 10.1002/pld3.140
|View full text |Cite
|
Sign up to set email alerts
|

Simple sequence repeat analysis of new potato varieties developed in Alberta, Canada

Abstract: The worldwide demand for potato production requires the constant development of new potato varieties with improved yield, quality, disease resistance, and abiotic tolerance. However, cultivar registration is preceded by a long process to morphologically and physiologically characterize the plants. Notably, this process can be expedited by DNA marker analysis. Simple sequence repeats ( SSR s), also known as microsatellites, are the most common reliable D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Potato genetic diversity is mainly estimated with morphological and physiological characteristics, such as plant architecture, resistance to diseases, and shape and color of flowers and tubers. However, many of these characteristics are affected by the environment [ 5 , 9 ]. Therefore, methodologies such as molecular markers, which are not affected by the environment, are currently used for the estimation of genetic variability in plant species because of their neutrality, Mendelian inheritance and ease of detection in any tissue and growth stage in plants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potato genetic diversity is mainly estimated with morphological and physiological characteristics, such as plant architecture, resistance to diseases, and shape and color of flowers and tubers. However, many of these characteristics are affected by the environment [ 5 , 9 ]. Therefore, methodologies such as molecular markers, which are not affected by the environment, are currently used for the estimation of genetic variability in plant species because of their neutrality, Mendelian inheritance and ease of detection in any tissue and growth stage in plants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also worked with SSR markers, such as Wang et al (2019) who proposed the model-based structure analysis, discriminating the population into two major subgroups, which can be further subdivided into seven groups based on collection sites Berdugo-Cely et al (2017) analysed 809 Andigenum group accessions from the CCC using 5968 SNPs to determine the genetic diversity and population structure of the Andigenum germplasm, as well as the usefulness of this collection to map qualitative traits across the potato genome, showing that the CCC can be subdivided into two major groups associated with their ploidy level, viz., Phureja (diploid) and Andigena (tetraploid). Tillault and Yevtushenko (2019) fingerprinted 20 potato varieties, including five new genotypes developed in Alberta, Canada, using 10 SSR markers selected for their high discriminatory power. In that study, STM0037, STM1016, and STM1104 were found to be the best SSR markers to detect genetic differences between potato varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Since representatives of the complex of the genus Rosa L. are part of the CSBG collection of biological resources, the evaluation of rose varieties using the molecular genetic method has begun. ISSR marker molecular genetic technique, widely spread to differentiate breeding material in various plant species [4][5][6], was used in the work. Molecular markers are characterized by a high level of polymorphism between varieties and can be effectively applied to assess general genetic characteristics.…”
Section: Introductionmentioning
confidence: 99%